THE SUBSTANTIATION OF THE PARAMETERS OF THE CENTRIFUGAL DEVICE FOR DISTRIBUTION OF THE MINERAL FERTILIZERS AT A REVERSING GEAR OF THE DISKS - V. CHERNOVOLOV; V. LUKHANIN; E. POVOLOTSKAYA (Advanced Engineering Research)
The modeling done under the programme «DISK-REVERSE» allows to build the diagrams of dependence of the basic digital output parameters of the disk from the factors characterizing a place of giving, an angle of an inclination and direction of the disk rotation. The given digital output characteristics for work of the device on a field in calm, with wind protection and on a slope can be received by changing the digital input factors. Reversing disk rotation allows to reduce a range of diapason of the manure guide or the range of regulation of an angle of boards inclination.